Spitfire - Flack, Jeremy (London Chancellor Press, 1994)
Including many air-to-air shots, this celebration of the Spitfire offers a photographic portfolio of one of the most celebrated examples of aerodynamic art, as well as a highly successful fighter plane remembered for its vital role in the fight against Nazi Germany in the long, hot summer of 1940.
Include Illustrations
Keywords: Spitfire (Fighter plane)